A morphological analysis-based creativity approach to identify and develop ideas for BMI: a case study of a high-tech manufacturing company. (1st January 2014) - Seidenstricker, Sven; Linder, Christian
Practice has shown that new businesses have succeeded in changing the structure of market sectors and opening positions of power through business model innovation. The reasons have been many, but include new technological possibilities, innovative products, changes in the supply chain management, optimised cost structures and unique resources. Regarding entrepreneurship and innovation management, it has become of interest to learn how such potentials can be unlocked and implemented using business model innovations. Here, the development of ideas plays an important role as it usually the first stage of each innovation and utilisation process. However, to date, research in the field of business models has not sufficiently answered the question. While this phase of development is assigned great significance, methodological support regarding existing procedures and process models have not, however, been given. Thus, the subject of this paper is the development of a method of systematically generating business model ideas based on morphological thinking. This includes guaranteeing consistency of the ideas developed as well as structured selection. The method was applied within a high-tech company.